Comparison of the efficiency of selected European banking sectors - Černohorská, Liběna (Masarykova univerzita, 2016)
There is no generally accepted concept of efficiency nor is there a uniform system of indicators for measuring bank efficiency. It is even possible to use the method of financial analysis to measure bank efficiency. In this paper, the following ratios are used for measuring bank efficiency: ROA, ROE, total assets, nonperforming loans/total loans, quick liquid assets/total assets, quick liquid assets/short-term liabilities, loans/deposits, and capital adequacy. The goal of this paper is to assess the efficiency of Czech banks using cluster analysis on the basis of selected ratios and to conduct a comparison with bank efficiency in Poland, Austria, Greece, Portugal, France, and Slovakia. The collective ratios for the entire banking sector will be compared for the selected countries for the years 2010–2014. The cluster analysis demonstrates that the Czech banking sector is the most similar to the Slovakian sector. According to a combination of selected ratios, it is possible to designate the cluster composed of the Czech and Slovak banking sectors as being the cluster with the highest banking sector efficiency. It differs extensively from the cluster of Greece and Portugal.
Komparace efektivnosti vybraných evropských bankovních sektorů
Keywords: banking sector; EU; efficiency; ROA; ROE; bankovní sektor; EU; efektivnost; ROA; ROE